The impact of International remittances on Gross Fixed Capital Formation in Kenya: Evidence from an autoregressive distributed lag modelling approach - Cyprian Amutabi (Cogent Business & Management, 2023)
AbstractDespite the general increase in remittance inflows in Kenya over the last four decades, it remains unknown as to whether part of these remittances forms an integral portion of productive investment in the aggregate economy. We, therefore, examined the impact of foreign remittances on Gross Fixed Capital Formation (GFCF) in Kenya using the ARDL model and time-series data for the period 1980–2020. We also sought to establish the direction of causality between the two variables and whether structural breaks mattered in modeling the remittances-GFCF relationship. First, we found that while remittances significantly reduced GFCF in the short run, their impact was insignificant in the long run. Secondly, the Granger Causality test showed evidence of a uni-directional causality running from remittances to GFCF. Thirdly, structural breaks significantly and positively moderated the remittances-GFCF nexus in Kenya; highlighting the importance of testing for structural breaks when analyzing a remittance-GFCF model. To promote remittance inflows in Kenya, there is a need to develop a robust financial system to facilitate the optimal harnessing of investment benefits accruing from such remittances. Further, and owing to the negative impact of remittances on investment in the short run; remittance-receiving households need to be sensitized on the productive use of remittances to ensure that they are forward-looking and, thus, use their remittances on productive investments as envisaged by pure self-interest and tempered altruistic remittance motives.